Determination of material parameters for a sheet‐layered lamination stack - Baloglu, Maximilian Volkan; Willner, Kai (Proceedings in Applied Mathematics and Mechanics, 2017)
The numerical simulation of sheet‐layered lamination stacks is a challenging task in structural mechanics due to the layout of these components. Depending on the manufacturing process, these sheets are either linked together with the help of a bonding varnish or are just packed up and basically free to slip inside of the stack, which can result in a nonlinear deformation behavior. To avoid a full FE‐simulation incorporating every layer, homogenization can be applied to identify a surrogate material model to achieve the desired accuracy by gaining performance. In this paper, a transversely isotropic material model is analytically formulated for a lamination stack with isotropic sheets in contact, which is captured with the help of a linear penalty method. The resulting stress‐strain relation is compared to results obtained by a numerical homogenization.
Keywords: lamination stack; homogenization; material modelling; contact mechanics